2020
DOI: 10.7127/rbai.v13n4001084
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento De Mudas De Pepino Sob Restrição Hídrica E Doses De Esterco Bovino

Abstract: A baixa disponibilidade de água e o baixo teor de matéria orgânica no solo, são fatores limitantes à produção agrícola em regiões de clima árido e semiárido. Assim, objetivou-se avaliar diferentes doses de esterco bovino e níveis de água disponível no substrato, para a produção de mudas de pepino. O estudo foi realizado em casa de vegetação, avaliando-se dois níveis de água disponível no substrato (100 e 50%) e quatro doses de esterco bovino (0, 20, 40 e 60% do volume do substrato), arranjados em esquema fator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
2
0
0
1
Order By: Relevance
“…Regarding electrolyte leakage in the leaf blade (Figure 5B), the results demonstrate that irrigation at 125% ETr and a nitrogen application rate of 73% of the recommended dosage led to a minimal value of 24.30% leakage. Conversely, the highest value of 65.09% was observed in plants subjected to a water Sá et al (2019b) observed similar outcomes in a study assessing the effects of substrate water availability (100% and 50%) combined with four levels of bovine manure (0, 20, 40, and 60% of substrate volume) on cucumber crops. Their findings indicated that the highest relative water content was recorded in plants exposed to the 35.26% manure level and cultivated under 100% substrate water availability.…”
Section: Irrigation In the Amount Of 125% Etr Combined With Nitrogen ...supporting
confidence: 69%
See 1 more Smart Citation
“…Regarding electrolyte leakage in the leaf blade (Figure 5B), the results demonstrate that irrigation at 125% ETr and a nitrogen application rate of 73% of the recommended dosage led to a minimal value of 24.30% leakage. Conversely, the highest value of 65.09% was observed in plants subjected to a water Sá et al (2019b) observed similar outcomes in a study assessing the effects of substrate water availability (100% and 50%) combined with four levels of bovine manure (0, 20, 40, and 60% of substrate volume) on cucumber crops. Their findings indicated that the highest relative water content was recorded in plants exposed to the 35.26% manure level and cultivated under 100% substrate water availability.…”
Section: Irrigation In the Amount Of 125% Etr Combined With Nitrogen ...supporting
confidence: 69%
“…X and Y-Nitrogen rates and Water replenishment levels, respectively. Sá et al (2019b) observed similar outcomes in a study assessing the effects of substrate water availability (100% and 50%) combined with four levels of bovine manure (0, 20, 40, and 60% of substrate volume) on cucumber crops. Their findings indicated that the highest relative water content was recorded in plants exposed to the 35.26% manure level and cultivated under 100% substrate water availability.…”
Section: Irrigation In the Amount Of 125% Etr Combined With Nitrogen ...supporting
confidence: 57%
“…Essa última quando mal manejada implica em risco de estresse hídrico, tais como: elevadas necessidades instantâneas de água por massa radicular, reduzido volume de água no substrato disponível para a planta e importância relativa dos fenômenos de advecção. Porém apesar da importância do suprimento das necessidades hídricas das mudas, poucas pesquisas têm sido desenvolvidas com relação a esse tema (MELO JÚNIOR et al, 2015;SÁ et al, 2017;SÁ et al, 2019). Com isso, objetivou-se avaliar a matéria orgânica no crescimento inicial e status hídrico do quiabeiro em condições de déficit hídrico.…”
Section: Introductionunclassified